2016
DOI: 10.25026/jtpc.v3i4.116
|View full text |Cite
|
Sign up to set email alerts
|

Riset Sitotoksik Campuran Ekstrak Daun Sirsak (Annona muricata L) dan Kulit Buah Manggis (Garcinia mangostana L) pada Sel Vero dan AML12

Abstract: ABSTRAKCampuran Daun sirsak dan Kulit buah manggis sekarang ini banyak digunakan sebagai fitoterapi penyakit kanker dan antioksidan. Tetapi penggunaan bahan ini belum diketahui data keamanannya. Tujuan dilakukan penelitian adalah untuk mengetahui efek sitotoksik campuran ekstrak daun sirsak dan kulit buah manggis terhadap sel vero dan sel AML12. Uji sitotoksik dapat memprediksi keberadaan senyawa yang bersifat toksik secara in vitro menggunakan sel normal atau sel yang telah mengalami transformasi. Uji ini men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Positively charged amino groups in chitosan that interact with negatively charged cell membranes will also form a layer that is capable of inhibiting ion channel transformation and inhibiting the work of enzymes in cells, so that cells will lack any nutrients and may contribute to cell death. 15 Haruan fish scale chitosan contains antioxidants that may reduce the activity of free radicals such as hydrogen peroxide, superoxide anions, and Cu2+ ions by binding to free radical ions. Antioxidants in chitosan have two types of mechanisms in inhibiting the oxidation process or stopping the reaction of free radicals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Positively charged amino groups in chitosan that interact with negatively charged cell membranes will also form a layer that is capable of inhibiting ion channel transformation and inhibiting the work of enzymes in cells, so that cells will lack any nutrients and may contribute to cell death. 15 Haruan fish scale chitosan contains antioxidants that may reduce the activity of free radicals such as hydrogen peroxide, superoxide anions, and Cu2+ ions by binding to free radical ions. Antioxidants in chitosan have two types of mechanisms in inhibiting the oxidation process or stopping the reaction of free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 The results of the research carried out by Saputra and Kroesnadi (2020) found that chitosan was not toxic to BHK-21 fibroblast cells. 15 Chitosan toxicity may be determined by identifying the degree of deacetylation, a degree of more than 35% will indicate low toxicity, whereas if the degree of deacetylation is below 35%, the toxicity depends on the dose of chitosan used. In regards to SNI, the value of the deacetylation degree of chitosan is 75%, while the chitosan in haruan fish scales has a degree of deacetylation of 85.25%, which indicates low toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the cytotoxicity of natural ingredients, in cases where IC 50 > 1000μg/mL, they are classified as non-toxic. 18 The final cytotoxicity test result provided information about the percentage of cells which had been able to survive. 15 This data proved that ethanol extract of Binjai leaves administered by MTT assay method was not cytotoxic to Vero cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these cells are highly stable, sensitive, and easy to culture. 14 The toxic effect of an extract is usually reported as the half maximal inhibitory concentration (IC50) which indicates the presence or absence of toxic potential of the extract. 15 The in vivo toxicity test is a procedure used to assess toxic effects of an extract on test laboratory animals by administering specific doses.…”
Section: Introductionmentioning
confidence: 99%